Perancangan Mesin Mixer Pakan Ternak dengan Watering system - Imantoro, Syahrul Huda; Dewi, Rany Puspita; Purnomo, Sigit Joko (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Manual mixing of animal feed in small-scale farms often results in non-homogeneous mixtures and requires a considerable amount of time. In addition, the addition of liquids such as vitamins or molasses is generally performed manually, leading to imprecise measurements. This study aims to design a 25 kg capacity animal feed mixer machine integrated with an automatic watering system to improve feed efficiency and quality. The research methods include machine element calculations, design modeling using SolidWorks, and structural strength simulation through static simulation analysis. The design results in a mixing chamber with dimensions of 0.40 m × 0.30 m × 0.325 m, driven by a 0.71 HP electric motor with a shaft rotation speed of 115 rpm. The automatic watering system is capable of supplying 3 liters of liquid within 44.96 seconds, ensuring an ideal moisture content of the feed. Structural strength simulation shows a maximum stress of 72.3 MPa on the frame with a Safety Factor of 5.0, while the mixing chamber experiences a maximum stress of 38.57 MPa with a Safety Factor of 9.1. These results indicate that the machine design is safe to operate and can serve as an appropriate technological solution to enhance feed productivity for farmers.